Coordenação de características funcionais dos órgãos abaixo e acima de solo e seu efeito na performance de árvores distribuídas em um gradiente hidrológico na Amazônia Central - Cordoba, Edher Checa (Instituto Nacional de Pesquisas da Amazônia - INPA, 2025)
Understanding the functional traits of trees and their influence on performance is essential to predicting how tropical forests will respond to climate change. In the Amazon, understanding the water mechanisms that support resilience strategies is especially relevant given the increasing frequency and intensity of droughts. Although many studies have focused on leaves and stems, the functioning of the belowground component—especially roots—remains little explored. This project investigates the coordination between root functional traits, their relationships with leaf features, along a hydro-edaphic gradient, and how the vertical distribution of fine root biomass affects the “terra firme” forests of Central Amazonia, where the water table is shallow. The central hypothesis proposes that variation in water table depth modulates both the coordination of functional traits and rooting depth, affecting aboveground attributes such as forest structure. The study is divided into three chapters: - Chapter 1: Assessment of the coordination between morphological and anatomical traits of fine roots. – Chapter 2: How the coordination of root traits relates to leaf traits across environments and within generalist tree species; and Chapter 3: Analysis of the vertical distribution of root biomass at different depths and hydrological environments. Collections were conducted at the Ducke Reserve and in plots along BR-319, encompassing different water conditions. The results revealed significant adjustments in morphological characteristics and rooting depth between environments. Two functional strategies were identified: "outsourcing," predominant in lowlands, with thicker roots and greater mycorrhizal colonization; and "do-it-yourself," common on plateaus, with thinner and more branched roots. Coordination between root traits was stronger in lowlands. Between root and leaf traits, there is a strong hydraulic trade-off between efficiency and safety in water transport. At a regional scale, excess soil water restricts the distribution of fine roots to the surface layers, leading to greater allocation of belowground biomass and forest structures with a high density of smaller trees. In less waterlogged areas, opposite patterns are observed. Although nutrient availability influences biomass partitioning, water table regimes strongly modulate this effect. The discovery that water regime exerts pervasive control over fine root distribution challenges the dominant nutrient- and climate-centric view, offering new insights for ecological modeling and forecasting the Amazon's role in biogeochemical cycles and carbon storage.
Keywords: Ecologia funcional; Árvores tropicais; Amazônia Central